Spousal bereavement is associated with more pronounced ex vivo cytokine production and lower heart rate variability: Mechanisms underlying cardiovascular risk?. (July 2018) - Fagundes, Christopher P.; Murdock, Kyle W.; LeRoy, Angie; Baameur, Faiza; Thayer, Julian F.; Heijnen, Cobi
Highlights: Those who were spousally bereaved had lower HRV than those who were not bereaved. Widowers had higher ex vivo cytokine production than non-bereaved age-matched controls. These findings add to the growing literature revealing the mechanisms that underlie bereavement-related cardiovascular problems. Abstract: The loss of a spouse is a highly stressful event that puts people at excess risk of mortality. Excess mortality among those who are widowed is highest in the first six months after the death of a spouse and decreases over time. Heart disease accounts for the largest proportion of these deaths. The psychological stress associated with stressful life events can enhance inflammation and lower heart rate variability (HRV). Both lower HRV and higher inflammation are risk factors for cardiovascular morbidity and mortality. Thirty-two recently bereaved individuals (Mean = 89.68 days since death, SD = 17.09) and 33 age-matched comparisons completed a blood draw, EKG, and self-report questionnaires. In both adjusted and unadjusted models, spousal bereavement was associated with enhanced pro-inflammatory cytokine production by in vitro lipolysaccharide-stimulated peripheral blood leukocytes. Moreover, spousal bereavement was associated with lower HRV in comparison to the comparison group. This study is the first to demonstrate that bereavement is associated with a more pronounced ex vivo cytokine production and lower HRV in a population that exclusively consisted of widows and widowers. These findings add to the growing literature revealing the mechanisms that underlie bereavement-related cardiovascular problems. Future longitudinal studies are needed to determine the temporal relation between these risks. Understanding the biological mechanisms that underlie this stressful life event could allow researchers to create therapeutic targets for interventions to reduce or prevent the toll of a "broken heart."